Breast surgical pathology in children and adolescents - Santino Figueroa, Ángel (2014)
Background: Breast pathology in children and adolescents is rare and usually benign. Most require only medical treatment and observation; however, some can have surgical indications. Objectives: To determine the 10-year experience at Hospital Infantil de Mexico's breast clinic in treatment of breast pathology in children. Design: Retrospective, trasversal and descriptive study. Setting: Hospital Infantil de Mexico Federico Gomez, Mexico DF. Participants: Patients 2 to 18 year-old. Methods: Search of medical files of breast pathology treated surgically in the period 2001-2011. Main outcome measures: Breast pathology and surgical treatment. Results: In 159 patients the most frequent pathology on females was fibroadenoma, and gynecomastia in males. Fibroadenomata and adenomata were treated by total surgical excision, polimastia by resection, gynecomastia by subcutaneous mastectomy, fibrocystic breast disease by simple excision or subcutaneous mastectomy, virginal mammary hypertrophy by subcutaneous mastectomy or mammary reduction, and giant fibroadenoma by simple excision, subcutaneous mastectomy or mammary reduction. Conclusions: We consider that most breast pathology in children is usually benign and can be treated satisfactorily by adequate surgery. Although with low incidence malignant breast disease is also possible in this age group.